Ingestion kinetics of mixotrophic and heterotrophic flagellates. Issue 4 (27th February 2023) - Edwards, Kyle F.; Li, Qian; Steward, Grieg F.
Abstract: In sunlit waters, significant predation is performed by unicellular, phagotrophic mixotrophs, that is, predators that also possess plastids. The success of a mixotrophic lifestyle will depend in part on how well mixotrophs acquire prey relative to specialized heterotrophs. Likewise, consequences of mixotrophy for productivity and element cycling will depend on the rate and efficiency at which mixotrophs consume prey biomass relative to heterotrophs. However, trait differences between mixotrophs and heterotrophs are not well characterized. In addition, cell size of mixotrophs varies widely, and constitutive mixotrophs include small flagellates deriving from diverse taxa, while larger species are primarily dinoflagellates. To determine whether similar constraints apply to phagotrophs across this broad range of size and taxa, we compiled 83 measurements of flagellate functional responses and compared maximum clearance rates ( C max ) and maximum ingestion rates ( I max ) between trophic modes. We found that the average mixotroph has a 3.7‐fold lower C max and 7.8‐fold lower I max than the average heterotroph, after controlling for cell size. The smaller penalty for C max suggests that relative fitness of mixotrophs will be enhanced under dilute prey concentrations that are common in pelagic ecosystems. We also find that growth efficiency is greater for mixotrophs and for flagellates with lower C max, indicating a spectrum of trophic strategies that may be driven by phototrophy vs. phagotrophy allocation as well as fast vs. slow metabolic variation. Allometric scaling shows that I max is constrained by a common relationship among dinoflagellates and other taxa, but dinoflagellates achieve a greater volume‐specific C max . These results should aid in interpreting protistan communities and modeling mixotrophy.